Tuning of polymeric membranes to mitigate fouling and removal of dissolved compounds for wastewater treatment: a Review - Tarun, S. S.; Dakshesh, S. K.; Arthanareeswaran, G. (Frontiers in Membrane Science and Technology, 2024)
Wastewater, referred to as sewage, has been a byproduct of human settlement since ancient times. An increase in human activities leads to more wastewater effluents, resulting in higher concentrations of organic compounds, which are harmful to all forms of living organisms and drinking water purposes. Traditional methods cannot satisfy this issue for higher concentrations. The advanced membrane process is an alternative to this conventional method for removing organic compounds and various effluents due to its high permeate quality and less toxicity. Moreover, the modification of polymeric membranes by increasing its content led to a higher flux thereby enhancing the fouling property for effective wastewater treatment. The processes, UF, RO, NF, and FO, ion exchange, MD, and pervaporation, were developed for more robust methods to improve the quality of the environment and lead to higher salt rejection. This review provides an overview of the fabrications, methods and modifications of substrates utilized in different processes with varying modules to achieve a higher flux rate, lowering the fouling. We discuss the materials used for various membrane modules in ceramic membranes under different operating circumstances and the methods to enhance the performance of membrane fouling. This review also aims to track the ongoing research works to broaden different process combinations for further research purposes, showcasing better antifouling performance and maximizing water quality in the future.